Perception of quality of life among community in Selangor - Rosli, Nur Farhanah; Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (Malaysian Institute Of Planners, 2018)
The quality of life (QOL) is a subjective matter that diversely defined by scholars. Since 1930s researchers from various fields have expressed their interest in the definition of QOL especially on the methods of investigation and measurement of QOL. Over more than four decades, Malaysia has made remarkable achievements regarding its economic growth as well as its socio-economic development. Numerous factors have been identified that may influence the quality of life of the people according to their personal preferences. For example, the perception or the satisfaction on the quality of an engineer may differ from an individual working as a teacher. Hence, how an individual measures their own quality of life can be different between another. The definitions and the method of assessing quality of life among communities are numerous and varied. This article assessed the perception of respondents on the quality of life among communities living in Selangor. The research objectives are to identify the current living condition in Selangor and to assess the level of satisfaction towards the living condition by the respondents living in Selangor. The study used quantitative research method where 500 respondents living in Selangor were surveyed and the questionnaire for the study comprises of questions on the satisfaction of living condition within the respondent areas. The preliminary analysis identified that the perception on the quality of life are significantly influenced by the respondent’s socio-economic background. Recommendation such as improvement in the physical conditions and continuous maintenance of the surrounding area within the neighbourhood were highlighted by the community as methods to improve the current living standard towards a better quality of life of the communities.